1976
DOI: 10.1128/aac.10.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Propionibacterium acnes and Related Microbial Species

Abstract: The minimal inhibitory concentrations of 32 antimicrobial agents were established for 73 strains of Propionibacterium acnes and four related species (P. granulosum, P. avidum, Corynebacterium minutissimum, and C. parvum). Most strains showed good susceptibility to those agents usually considered active against gram-positive organisms. With the exception of C. minutissimum, the strains tested revealed more or less identical susceptibility ranges. The lowest minimal inhibitory concentrations were observed with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
20
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 11 publications
6
20
0
Order By: Relevance
“…The MIC values reported here confirm those obtained in other studies, where few strains with an MIC >6.25 pg/ml have been isolated and most were inhibited at lower concentrations. The greater sensitivity of strains to minocycline compared with tetracycline (Chow et al, 1975;Hoeffler, KO and Pulverer, 1976) was also confirmed. In contrast with the generally low levels of tetracycline resistance, the strains of P. acnes isolated by Guin et al (1979) with MIC values > 25 pg/ml are of interest.…”
Section: Discussionmentioning
confidence: 72%
“…The MIC values reported here confirm those obtained in other studies, where few strains with an MIC >6.25 pg/ml have been isolated and most were inhibited at lower concentrations. The greater sensitivity of strains to minocycline compared with tetracycline (Chow et al, 1975;Hoeffler, KO and Pulverer, 1976) was also confirmed. In contrast with the generally low levels of tetracycline resistance, the strains of P. acnes isolated by Guin et al (1979) with MIC values > 25 pg/ml are of interest.…”
Section: Discussionmentioning
confidence: 72%
“…Improvement in acne is often achieved by long-term administration of broad-spectrum antibiotics which are thought to decrease the density of propionibacteria (1, 12,14) and hence reduce the free fatty acids in the sebum (7,18). At present, there are few reports describing the effects of antibiotics on propionibacteria in vitro, those that do exist being mainly concerned with the evaluation of antimicrobial susceptibility (9,19). In a recent publication, however, Webster et al (26) found that lipase production in vitro by a strain of Propionibacterium acnes was inhibited by subgrowth-inhibitory concentrations of tetracycline and declomycin and delayed by erythromycin.…”
mentioning
confidence: 99%
“…The lowest antibiotic concentration at the end of CPB was 6 ,ug/ml after 5 h of surgery in one patient who received CP. This value is still many times the minimal inhibitory concentration of most contaminating staphylococci and diphtheroids (9,17).…”
Section: Resultsmentioning
confidence: 99%